"Lutar, aprender, vencer, trabalhar": Adult Literacy, Popular Education and Militant Networks in the Newly Independent Guinea-Bissau - (:unkn) unknown (My University, 2022)
This article analyses the genesis, the development and the political and cultural stakes of adult literacy and rural popular education projects set up from 1975 onwards in Guinea-Bissau. Rooted in the legacy of the revolutionary schools developed by the African Party for the Independence of Guinea and Cape Verde (PAIGC) during the Liberation War (1963-1974), they were the result of collaboration between the new Ministry of Education and various foreign institutions. The Círculos de Cultura, developed by Paulo Freire and the Institute for Cultural Action (IDAC), and the Integrated Popular Education Centres (CEPI) set up by Roland Colin and the teams of the International Research and Training Institute for Education and Development (IRFED), were important pedagogical innovations. They were also the scene, in a historical context marked by the fall of Portuguese colonialism, the political exile of Latin American activists, the rise of Liberation theology and the height of Third Worldism, of a resignification of militant ideological commitments, analysed here through the prism of unpublished sources.
Keywords: African Research